2010
DOI: 10.1002/ejoc.200900848
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Diameter‐Selective Functionalization of SWCNTs with Lithium Alkynylides

Abstract: Covalent functionalization by addition to the sidewalls ofsingle‐walled carbon nanotubes (SWCNTs) is one of the most important methods for the derivatization of carbon nanotubes. The nucleophilic addition of organometallic reagents (carbon‐ and nitrogen‐based carbanions) has recently become a widely used tool for the introduction of functional moieties onto the surface of this new carbon allotrope. The extension of this concept by the successful nucleophilic addition of in situ generated lithium acetylides to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…The larger diameter (12,3) nanotubes show maximum recovery of their RBM signals with pyrolysis at 350 °C, whereas temperatures greater than 500 °C appear necessary for full restoration from the smaller diameter (7,5) nanotubes. Additional data for the (10,3) and (8,3) species are included in Supporting Information. It seems clear that the pattern of recovery of the RBM Raman bands shows structure-dependent defunctionalization rates, with the largest diameter SWCNTs most readily losing their dodecyl addends.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger diameter (12,3) nanotubes show maximum recovery of their RBM signals with pyrolysis at 350 °C, whereas temperatures greater than 500 °C appear necessary for full restoration from the smaller diameter (7,5) nanotubes. Additional data for the (10,3) and (8,3) species are included in Supporting Information. It seems clear that the pattern of recovery of the RBM Raman bands shows structure-dependent defunctionalization rates, with the largest diameter SWCNTs most readily losing their dodecyl addends.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 The main such pattern is enhanced reactivity of smaller diameter nanotubes because of their greater sp 2 bond strain. 10 Although previously unexplored, variations in reactivity with structure should also affect the process of covalent defunctionalization, in which bonds to addends are broken to regenerate pristine SWCNTs.We report here a structure-resolved study of thermally induced defunctionalization reactions.Pristine SWCNT samples were first subjected to Billups-Birch reductive alkylation to obtain substantial sidewall functionalization with docedyl groups and solubility in organic solvents. 3,5 These dodecylated samples were then pyrolyzed for specific times at a range of controlled temperatures, after which changes in composition were monitored by optical absorption, fluorescence, and Raman spectroscopies and gravimetric analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent and non-covalent chemical functionalization approaches play a fundamental role to debundle and stabilize CNTs in solution where their unique characteristics can be discerned and studied. Reagents, such as oxidants [6], diazonium salts [7][8], carbenes [9], nitronium ions [10], lithium alkynylides [11], and azomethine ylides [12], have been successfully employed for the covalent modification of CNTs. Despite this rich functionalization chemistry [13][14][15][16][17], only a few comparative studies [11,18] on the addition chemistry to CNT have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Reagents, such as oxidants [6], diazonium salts [7][8], carbenes [9], nitronium ions [10], lithium alkynylides [11], and azomethine ylides [12], have been successfully employed for the covalent modification of CNTs. Despite this rich functionalization chemistry [13][14][15][16][17], only a few comparative studies [11,18] on the addition chemistry to CNT have been reported so far. Motivated by this, we have evaluated the solubility and functionalization degree (FD) of single-wall carbon nanotube (SWCNT) samples that were subjected to different functionalization protocols through a continuous-flow approach.…”
Section: Introductionmentioning
confidence: 99%